Investigation of the Mechanism by Which Herpes Simplex Virus Type 1 LAT Sequences Modulate Preferential Establishment of Latent Infection in Mouse Trigeminal Ganglia - Imai, Yumi (American Society for Microbiology (ASM), 2009)
We previously demonstrated that herpes simplex virus type 1 (HSV-1) preferentially establishes latent infection in monoclonal antibody (MAb) A5-positive ganglionic neurons and that a 2.8-kb portion of the HSV-1 genome, corresponding to the 5′ end of the LAT (latency-associated transcript) coding region, is responsible for this phenotype (38, 65). In the current study we carried out further genetic mapping of this latency phenotype and investigated some of the mechanisms that might be responsible. Studies with the chimeric virus HSV-1 17syn+/LAT2, an HSV-1 virus engineered to express HSV-2 LAT, demonstrated that this virus exhibited an HSV-2 latency phenotype, preferentially establishing latency in MAb KH10-positive neurons. This result is complementary to that previously described for the chimeric virus HSV-2 333/LAT1 and indicate that the HSV-1 latency phenotype can be changed to that of HSV-2 by substitution of a 2.8-kb piece of complementary viral DNA. Sequential studies in which we evaluated the pattern of HSV-1 latent infection of the mouse trigeminal ganglion following ocular inoculation with viruses with deletions of functional thymidine kinase, glycoprotein E, ICP0, and US9 protein demonstrate that preferential establishment of HSV-1 latent infection in A5-positive neurons is not a consequence of (i) differential access of HSV-1 to A5-positive neurons,(ii) differential cell-to-cell spread of HSV-1 to A5-positive neurons, (iii) differential “round-trip” spread of HSV-1 to A5-positive neurons, or (iv) expression of ICP0. Additional mapping studies with the HSV-1 LAT deletion viruses dLAT371, 17ΔSty, and 17Δ348 indicate that most of the LAT 5′ exon is not required for HSV-1 to preferentially establish latent infection in A5-positive neurons.